ANALYSIS OF VULNERABILITY POLLUTING GROUNDWATER BY USING SINTACS METHOD AND DETERMINATION OF PRIORITY SCALE CONTROL OF GROUNDWATER VULNERABILITY IN CIMAHI CITY - GARNADI SURYADI (NIM : 25314706), GILANG
Groundwater vulnerability maps have become standard tools for protecting groundwater sources from pollution and are invaluable in decision-making processes related to land use planning. The assumption that the physical environment affects the level of groundwater protection against pollutants and enters the subsurface environment. One method of making groundwater pollution vulnerability maps is the SINTACS method. SINTACS method can predict the susceptibility of groundwater pollution that has 7 parameters. Data analysis was performed using Arcgis 10.3. An exploration-oriented study on field and multicriteria field excavation in selecting alternative models or strategies to optimize the performance of groundwater susceptibility strategies. Firstly done to study theory and research first then conducted a survey that is charging kuisoner to collect sample data at a certain time from some expert respondents. The method used is AHP. The susceptibility of groundwater pollution in Cimahi City based on the assessment of the development method is divided into five classes of vulnerability ie very high, high, medium, low and very low zones. Very low zone of vulnerability of Cimahi City water pollution spread in 4 districts of Cipageran, Citeureup, Cibabat and Pasir Paliki. Low zone of vulnerability of groundwater contamination of Bandung City spread in 4 sub-districts namely Cipageran, Citeureup, Cibabat and Pasir Kaliki. Zone Medium susceptibility of Cimahi city water pollution spread in 10 District of Cipageran, Citeureup, Cibabat, Pasir kaliki, Cimahi, Padasuka, Setia Manah, Karang Mekar, Baros and Cigugur. High Zone of Cimahi City's water pollution vulnerability spread in sub-districts of Cibeureum, Melong, Main, Leuwi Elephant, Cibeber, Padasuka. Very High Zone of Cimahi City's Crime Pollution vulnerability spread in sub-districts of Cibeureum, Cigugur, Baros, Main, Leuwi Elephant, Cibeber, Padasuka Cipageran, Citeureup. Selected five options categories that become popular choice in the eyes of experts, in sequence ie limit of debit, application of AMDAL, regulation of location density, determination of zone of taking and application of Economic instruments